Implementasi alat pengusir hama sawah dengan cara tradisional dan modern bertenaga surya menggunakan sensor PIR berbasis Android - balle, joddy lintar; Fauzan, Mochamad Farras; Ridwan, Ridwan Siskandar; Shubhi, Muhammad Shubhi Maulana; Triya, Tria Febriyanti; Vandame, Vandame Ronald Suhada; Alif, Naufal Alif Falah; mira, Mira Fitria Dewi; Diana, Diana Putri Rahmani; merry, Merry Ardelia Wirastuti; Nabila, Nabila Fakhiratunisa; Kaisar, Kaisar Renaisance Al-ars (Jurnal Sains Indonesia, 2021)
The development of existing technology, of course, by making technological innovations in the form of tools that can help farmers in protecting their fields from pests. This tool works automatically by using a motion sensor combined with a scarecrow which will produce Movement output for the scarecrow, with the hope of scaring off pests, especially birds, as well as farmers who use Traditional. With the aim of creating a tool that works automatically to repel pests efficiently and effectively. Because it will combine traditional and modern methods. The application of mouse and bird repellents to rice plants based on solar energy.